Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Maltooligosaccharide forming amylases and their applications in food and pharma industry - Shinde, Vidhya K.; Vamkudoth, Koteswara Rao (Journal of Food Science and Technology-Mysore, 2022)
Oligosaccharides are low molecular weight carbohydrates with a wide range of health benefits due to their excellent bio-preservative and prebiotic properties. The popularity of functional oligosaccharides among modern consumers has resulted in impressive market demand. Organoleptic and prebiotic properties of starch-derived oligosaccharides are advantageous to food quality and health. The extensive health benefits of oligosaccharides offered their applications in the food, pharmaceuticals, and cosmetic industry. Maltooligosaccharides and isomaltooligosaccharides comprise 2-10 glucose units linked by alpha-1-4 and alpha-1-6 glycoside bonds, respectively. Conventional biocatalyst-based oligosaccharides processes are often multi-steps, consisting of starch gelatinization, hydrolysis and transglycosylation. With higher production costs and processing times, the current demand cannot meet on a large-scale production. As a result, innovative and efficient production technology for oligosaccharides synthesis holds paramount importance. Malto-oligosaccharide forming amylase (EC 3.2.1.133) is one of the key enzymes with a dual catalytic function used to produce oligosaccharides. Interestingly, Malto-oligosaccharide forming amylase catalyzes glycosidic bond for its transglycosylation to its inheritance hydrolysis and alternative biocatalyst to the multistep technology. Genetic engineering and reaction optimization enhances the production of oligosaccharides. The development of innovative and cost-effective technologies at competitive prices becomes a national priority.
Keywords: Glycosyl hydrolases; Isomaltooligosaccharides; Maltooligosaccharide; Maltooligosaccharide forming amylase; Transglycosylation